New strategy for non-enzymatic determination of lactate via regeneration of cofactor NADH using flexible electrochemical sensors prepared with nitrogen-doped graphene oxide conductive ink - Dokur, Ebrar; Gorduk, Ozge; Sahin, Yucel (ELSEVIER, 2025)
This study presents a novel approach for non-enzymatic lactate detection by regenerating NADH using NAD+ instead of traditional enzymes or metal nanoparticles. The electrodes were fabricated from the developed conductive inks, demonstrating a clear correlation between the lactate concentration and NADH oxidation peak current. In this system, lactate functions not only as an analyte but also as a proton source, enhancing the regeneration of NADH during the electrochemical reduction of NAD+. The incorporation of nitrogen-doped graphene oxide into the conductive ink as a second proton source further improved NADH formation, increasing the overall efficiency of lactate detection. The electrodes were thoroughly characterized using cyclic voltammetry, electrochemical impedance spectroscopy, field-emission scanning electron microscopy, energy dispersive X-ray spectrometry, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The electrodes achieved detection limit of 2.11 mu M for lactate. Importantly, the developed electrodes successfully detected lactate in artificial sweat samples, thereby highlighting their practical applicability. This research not only advances the field of electrochemical biosensing, but also opens new avenues for monitoring lactate levels in biological and clinical settings, showcasing the potential of enzyme-free detection methods.
Keywords: Conductive ink; Flexible electrode; Lactate; Screen printed electrode; Lab-made; BIOSENSOR; NANOPARTICLES; ELECTRODES; REDUCTION; BINDER; Chemistry; Materials Science